The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/ijo.2017.269
|View full text |Cite
|
Sign up to set email alerts
|

Novel associations between blood DNA methylation and body mass index in middle-aged and older adults

Abstract: Together, these findings suggest that BMI is associated with blood DNA methylation at a large number of CpGs across the genome, several of which are located in or near genes involved in ATP-binding cassette transportation, tumour necrosis factor signalling, insulin resistance and lipid metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
95
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(105 citation statements)
references
References 54 publications
10
95
0
Order By: Relevance
“…cg21429551 and cg19390658 map to GARS , which encodes the ligase glycyl-tRNA synthetase. These CpGs were associated with smoking, BMI, triglycerides and HDL-C levels in our study and in previous reports [36,49,50]. Two previous candidate gene studies including both CpGs or cg21429551 alone have shown negative results regarding their association with CHD [32,36].…”
Section: Discussionsupporting
confidence: 76%
“…cg21429551 and cg19390658 map to GARS , which encodes the ligase glycyl-tRNA synthetase. These CpGs were associated with smoking, BMI, triglycerides and HDL-C levels in our study and in previous reports [36,49,50]. Two previous candidate gene studies including both CpGs or cg21429551 alone have shown negative results regarding their association with CHD [32,36].…”
Section: Discussionsupporting
confidence: 76%
“…We performed EWASs between BMI at two life points and blood DNA methylation, and found that methylation at several loci was associated with BMI at middle age, BMI at age 18-21 years and BMI change. Methylation at some of these loci, ZPLD1 10, 14 , SOCS3 12-16 , CRELD2 10, 13, 14 , NOD2 13, 14, 16 and PHGDH 9,13,14,16 , has been previously reported to be associated with BMI. Associations at the other loci, such as LY9, COL6A2, ZBBX, MAP3K13, CRH, etc., do not appear to have been previously reported.…”
Section: Discussionmentioning
confidence: 98%
“…For the AMDTSS, the model was additionally adjusted for family and zygosity as random effects. For the MCCS, the model was additionally adjusted for sample type (dried blood spots/mononuclear cells/buffy coats) and country of birth (Australia/UK/Italy/Greece) as fixed effects, and for study, plate and chip as random effects . For the AMDTSS, the Bioconductor package bacon was used to adjust for the observed inflation of test statistics.…”
Section: Methodsmentioning
confidence: 99%